Cost Control-Oriented Provisions in Croatian Pharmaceutical Policy - Voncina, Luka (World Bank, Washington, DC, 2020)
Croatia operates a mandatory health insurance system with a single public health insurance fund, the Croatian Health Insurance Fund (HZZO), acting as the sole public purchaser of health care services for all insured—the entire population of Croatia. The HZZO holds a monopsony on reimbursement and pricing of publicly funded medicines. This gives it leverage in negotiations with pharmaceutical companies. The HZZO implements two (brand name based) lists of medicines that define: (a) which products are reimbursed, (b) their wholesale prices, and (c) reimbursed prices and co-payments—the ‘basic’ list with medicines dispensed in community pharmacies and hospitals with no co-payments, and the ‘complementary’ list with medicines dispensed in community pharmacies covered partially through mandatory insurance and partially by co-payments. These out-of-pocket payments are the result of internal reference pricing procedures, implying that all medicines with co-payments should have comparable1 parallel products listed in the ‘basic list’ with no co-payments. Community pharmacies are reimbursed monthly for the products they dispense at the listed reimbursed prices. They procure medicines from wholesalers at the regulated wholesale prices (a maximum of 8.5 percent of which accounts for wholesale margins) and are in addition paid by the HZZO linear fees for dispensing. No retail margins are allowed for HZZO reimbursed medicines. Hospitals are paid through Diagnosis Related Groups (DRGs, that account for the cost of medicines used in treatment) but receive additional funds (100 percent of listed price) for use of medicines defined by the HZZO as expensive. Hospitals procure all medicines through public procurement. HZZO’s lists define the maximal prices they can pay in the process. Products not reimbursed by the HZZO (over the counter and prescription medicines) can be freely priced. Nevertheless, given the breadth of HZZO’s coverage, sales of non-reimbursed prescription medicines are marginal. The value-added tax (VAT) on all medicines (including those reimbursed by the HZZO) is set at 5 percent of the wholesale price.